Can occupational labor shortages be identified using available data? - Veneri, Carolyn M. (Monthly Labor Review, 1999)
The United States has enjoyed over seven years of expansion, which has led to widespread reports of labor shortages in certain occupations. Stories in newspapers across the country have claimed that there are unmet needs for information technology workers, construction laborers, craftworkers, registered nurses, qualified teachers, and others. However, no particular source of data exists to provide a measure of occupational shortages, so analysts generally depend on labor market data to corroborate anecdotal evidence. These data include trends in employment and earnings and employment rates for particular occupations. The writer discusses the meaning of occupational labor shortages and assesses the adequacy of available data in identifying, quantifying, and evaluating such shortages.